Managing the final journey home: exploring perceptions, experiences and responses to death among Congolese migrants in Johannesburg - Kwigomba, Darius (My University, 2014)
The study explores perceptions and responses of Congolese migrants when they experience the death of other migrants. The study takes an ethnographic qualitative approach and gathers data from three Congolese ethnic groups living in Johannesburg. This is done by observing and participating in their funeral ceremonies as well as interviewing community members. The primary objective of this study is to understand the cultural changes migrants experience as a result of migration by exploring social, economic and cultural challenges migrants encounter when experiencing death of a fellow migrant. Findings of this study indicate migrants strive to observe their home culture in the hosting country. Marginalisation is the acculturation strategy that explains their ways of dealing with death in South Africa. Results further indicate migrants’ perceptions of experiences and ways of dealing with death out of their places of origin are negatively annotated. This is due to difficulties in recreating elements of their own culture as well as the absence of people who are traditionally responsible for dealing with death among the migrant community. Lastly some causes of death, such as HIV/AIDS, are highly stigmatized. This study contributes to the scarce literature existent on the topic of perceptions and responses to death among migrants.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, Forced Migration, 2013